Secondary surveillance radar antenna - Schejbal Vladimír; Bezoušek Pavel; Pidanič Jan; Chyba Milan (IEEE (Institute of Electrical and Electronics Engineers), 2013)
This paper deals with a secondary surveillance radar (SSR) array antenna, which is intended for a system combining the secondary surveillance radar antenna and the primary surveillance radar antenna. It describes the patch array elements and the synthesis for the secondary surveillance radar array, considering both elevation and azimuth patterns for sum, difference, and sidelobe-suppression beams, and suspended stripline couplers. The utilization of multilayer techniques allows the connection of layers with patch radiating elements and layers with beamforming networks.
Anténa sekundárního přehledového radaru
Keywords: secondary surveillance radar (SSR); array antenna; antenna synthesis; patch antenna; stripline coupler; sekundární přehledový radar (SSR); anténní řada; anténní syntéza; patch anténa; páskový dělič